2014
DOI: 10.1002/nme.4808
|View full text |Cite
|
Sign up to set email alerts
|

A consistent u‐p formulation for porous media with hysteresis

Abstract: SUMMARYThis paper presents a continuum formulation based on the theory of porous media for the mechanics of liquid unsaturated porous media. The hysteresis of the liquid retention model is carefully modelled, including the derivation of the corresponding consistent tangent moduli. The quadratic convergence of Newton's method for solving the highly nonlinear system with an implicit finite element code is demonstrated. A u-p formulation is proposed where the time discretisation is carried out prior to the space … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 69 publications
(117 reference statements)
1
43
0
Order By: Relevance
“…The solution is then obtained with the finite element method [3,23,24]. Further details, especially on the derivation of all equations for porous media, are found in the works by de Boer, Ehlers, Lewis, Schrefler and Pedroso [13,14,25,22].…”
Section: Governing Equations and Numerical Solutionmentioning
confidence: 99%
See 3 more Smart Citations
“…The solution is then obtained with the finite element method [3,23,24]. Further details, especially on the derivation of all equations for porous media, are found in the works by de Boer, Ehlers, Lewis, Schrefler and Pedroso [13,14,25,22].…”
Section: Governing Equations and Numerical Solutionmentioning
confidence: 99%
“…It is observed that this order (time first, space later) yields great convenience when dealing with complex liquid retention models (e.g. with hysteresis) [22]. As shown in the following, the Newton-Raphson method can then be directly applied after deducing the derivatives related with the liquid retention model.…”
Section: Finite Element Solutionmentioning
confidence: 99%
See 2 more Smart Citations
“…The TPM can be consistently derived from continuum mechanics, thermodynamics, the theory of mixtures, and the concept of volume fractions . For the static and dynamic behaviour of porous media, simulations based on the TPM (and Biot theory) have generated a great deal of advances; see, eg, previous studies …”
Section: Introductionmentioning
confidence: 99%